Comparison Of Atherosclerotic Risk Factors In Patients With Secondary Amylodosis And Nephrotic Syndrome - Cure, Osman; Cengiz, Kuddusi (General Internal Medicine VI (Spring), 2024)
Objectivewe aimed to compare atherosclerotic risk factors in patients with secondary amyloid and nephrotic syndrome with proteinuria.Method In the nephrology outpatient clinic, patients with nephrotic syndrome clinic and proteinuria underwent diagnostic biopsy of the kidney and other tissues thought to be infiltrated with amyloidosis. Demographic, clinical, laboratory and biopsy results of the people included in the study were evaluated. ResultsA total of 89 people were included in the study (secondary amyloidosis: 12 female and 18 men, nephrotic syndrome: 12 female and 17 men, healthy control: 15 female and 15 men, mean age respectively: 46.5±14.2 year, 45.3±13.3 year, 45.4±5.7 year), Total cholesterol, triglyceride, low density lipoprotein cholesterol (LDL-C), lipoprotein a (Lp a), apo-lipoprotein Al (apo Al), apo-lipoprotein B (apo B), apo-lipoprotein E (apo E), C- reactive protein (CRP) and fibrinogen levels in nephrotic syndrome and secondary amylodosis patients were significantly higher than the control group whereas high density lipoprotein cholesterol (HDL-C) levels were lower (p<0.01). When nephrotic syndrome and secondary amyloidosis patients were compared, total cholesterol, triglyceride, LDL-C, HDL-C, apo Al, apo B and apo E levels were higher in the nephrotic syndrome group compared to the secondary amyloidosis group (p<0,05). There were no differences in CRP, fibrinogen and Lp(a) levels (p>0.05).ConclusionOur data showed that atherosclerotic risk factors were significantly higher in patients with nephrotic syndrome and secondary amyloidosis. Patients with amyloidosis should be closely monitored for other atherosiderotic risk factors as well as amyloid accumulated in the organs